Until dawn [videorecording (DVD)] - Dauberman, Gary; Butler, Blair; Rubin, Ella; A'zion, Odessa; Cimino, Michael, 1999-; Yoo, Ji-young; Cameli, Belmont; Mitchell, Maia; Stormare, Peter (Sony Pictures Home Entertainment, 2025)
One year after her sister Melanie mysteriously disappeared, Clover and her friends head into the remote valley where she vanished in search of answers. Exploring an abandoned visitor center, they find themselves stalked by a masked killer and horrifically murdered one by one...only to wake up and find themselves back at the beginning of the same evening. Trapped in the valley, they're forced to relive the night again and again only each time the killer threat is different, each more terrifying than the last. Hope dwindling, the group soon realizes they have a limited number of deaths left, and the only way to escape is to survive until dawn.